Vulnerability Index Elaboration for Climate Change Adaptation in Peru - Vieira, Marta Tostes; Vieira, Alfredo Villavicencio; García, Claudia Motta Villa (European Journal of Sustainable Development, 2019)
This paper evidences one of the most relevant information gaps of climate change adaptation in Peru: its vulnerabilities. First, it contextualizes main national level impacts and progress made in adaptation measures definition from prioritized thematic areas. Then, it addresses the difficulty of finding tools to measure climatic risk level. For instance, this arises the need to focus on the vulnerability associated with climate change adaptation efforts. Therefore, a vulnerability index based on a multi criteria analysis is proposed, with three parts. In the first one, three-work axes were chosen following the fifth IPCC report guidelines: climatic phenomena dangers, territorial exposure, and subjects’ vulnerability. The territorial area analysis was carried on at district level. With regard to subjects, five indicator groups were identified, and measurable variables were chosen: population; species and ecosystems; functions, services, and environmental municipalities’ assets; economic, social and cultural assets; and infrastructure. Next, data was searched for each variable and it was systematized in a multi-criteria database. Finally, an index (0-15) was developed to calculate socio-climatic vulnerability of all the Peruvian District Municipalities. They were classified according to social, climatic, and socio-climatic vulnerability range. This facilitates a targeting instrument for public policies that can generate better climate change risk management and contributes to commitments fulfillment of the Sustainable Development Goals. Keywords: Climate change, Vulnerability, Climate change adaptation, Socio-climatic vulnerabilities, Climate risk, Sustainable Development Goals